Optimizing 4-ary Huffman Trees and Normalizing Binary Code Structures to Minimize Redundancy and Level Reduction - Tonny Hidayat; Hendra Kurniawan; Ali Mustopa; Jeki Kuswanto (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2025)
Since the present data expansion and increase are occurring at an increasingly rapid pace, the solution of adding storage space is not sustainable in the long run. The growing need for storage media can be addressed with lossless compression, which reduces stored data while allowing complete restoration. Huffman remains a potent method for data compression, functioning as a